One-loop off-shell decay \(H^* → ZZ\) at future colliders - Phan, Khiem Hong; Tran, Dzung Tri; Nguyen, Anh Thu (Communications in Physics, 2023)
We present one-loop formulas for contributing to the \(HZZ\) vertex in 't Hooft-Veltman gauge within Standard Model framework. One-loop off-shell Higgs decay rates to \(Z\)-pair are investigated in both unpolarized and longitudinal polarization for \(Z\) bosons in final state. The corrections are range of $7%$ to 8.4% when we vary the off-shell Higgs mass from 200 GeV to $500$ GeV. In applications, we study off-shell Higgs decay \(H^* → ZZ\) in the Higgs productions at future colliders such as the signal processes \(γ^*(Q^2)γ → H^* → ZZ\) and \(e^-γ → e^-H^* → e^- ZZ\) are analyzed.